Economics of environmental management - Kolk, Ans. (Harlow, England ; New York: Financial Times Prentice Hall, 2000)
"Increasing attention to environmental management has raised many new dilemmas for firms. How can managers deal with environmental issues in a competitive situation that is international and heterogeneous? What are the strategic and financial implications of environmental management? How can they cope with regulation, considering the choices which range from compliance to voluntary initiatives? And how do other firms organise their environmental management and communicate with stakeholders?" "This book examines these different topics, without dogma or prescription. It demonstrates the complexity of an area in which there are often no right or easy answers.".
"This text is written for students interested in environmental management, and for managers, regulators and consultants who want to keep abreast of the latest developments."--BOOK JACKET.
1. Introduction to environmental management -- Pt. 1. Between Regulation and Self-Regulation. 2. Business perspectives on regulation. 3. International policy and voluntary initiatives. 4. Strategies and the environment -- Pt. 2. From Theory to Practice. 5. Environmental management systems and standards. 6. Environmental reporting. 7. Environmental management accounting / Mark van der Veen. 8. Dilemmas of environmental management.
Includes bibliographical references (p. 189-196) and index.
Keywords: Environmental management -- -- Economic aspects; Milieumanagement; Bedrijfsinterne milieuzorg; Gestion de l'environnement -- -- Aspect économique.; Économie de l'environnement.